Design and Performance Testing of Seawater Batteries as Renewable Energy for Marine Boat Lights - Dedtri Anwar; Jedithjah Naapia Tamedi Papia; Hendra Purnomo; Putu Deny Darmawan (Lamintang Education and Training (LET) Centre, 2025)
Indonesian seas offer abundant renewable energy potential. Seawater batteries have attractive advantages as a source of electrical energy. The purpose of this study was to design and manufacture a seawater battery and test its performance for ship lighting. The methodology used includes designing and manufacturing a seawater battery storage container based on electrode dimensions, assembling electrodes and insulators, and testing battery performance using LED lights. The results showed that the design produced an 8-cell seawater battery with a height of 24 cm and a diameter of 17.78 cm (7 inches). Performance testing with a 7 W LED lamp for 60 minutes showed that higher salt content caused an increase in the average light intensity produced. In 8 W and 10 W LED lamps, it is known that an increase in the average light intensity produced only occurs at an increase in salt content of 3 to 4%, while an increase in the average light intensity at a salt content of 5% does not occur, iii) average salt content -an average of 4% on a seawater battery with a 60 minute test for a 7W LED lamp produces an average light intensity of 227.33 lumens, for an 8W LED lamp an average of 325 lumens, and for a 10W LED lamp an average of 604, 67 lumens. The greater the power of the LED lamp used, the greater the light intensity produced.